The relationship between Hofstede’s cultural dimension towards working culture / Mohamad Shadeeq Sharun - Sharun, Mohamad Shadeeq (Faculty of Business and Management, 2014)
This research will focus on one of the factors that lead to working culture which is Hofstede’s Cultural Dimension. The study is conducted in Cohu, Inc. which located at Krubong, Melaka, Malaysia. The study done is to obtain as much information for better understanding the relationship between masculinity, power distance, uncertainty avoidance, and individualism with working culture. In order to completing this research, the hypothesis was been constructed and focused on the objective to determine whether there has significant relationship between those independent variable and working culture. For this research, workers from Cohu, Inc. were chosen as respondents. Questionnaire had been distributed to 100 workers. The data was obtained from the primary data of the questionnaire. All data collected through the questionnaires were analyzed systematically by Statistical Package for Social Science (SPSS).